Minimal Growth Requirements for Clostridium perfringens and Isolation of Auxotrophic Mutants - Sebald, Madeleine (1975)
The minimal growth requirements for two strains of Clostridium perfringens were defined, and both synthetic and semisynthetic plating media were developed. Plate counts of the wild-type strains on both of these minimal media were equivalent to those on complex media. A number of auxotrophic mutants of each strain were isolated, and their phenotypes were defined.